Preparation and Characterization of Activated Carbon Made from Robusta Coffee Skin (Coffea Canephora) - Raihan, Raudhatul; Setiawan, Adi; Hakim, Lukman; Muhammad, Muhammad; Arif, Muhammad; Hosseiniamoli, Hadi (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2020)
Indonesia is one of the coffee-producing countries where production tends to increase from year to year. Currently, residuals from coffee-fruit processing such as coffee-skin and husks are thrown away without any use and this biomass residual contains several toxic chemicals such as alkaloids, tannins, and polyphenols. One of potential uses of coffee-industry by-product is to make activated carbon (ACs), which is made through a carbonation process and followed by an activation process. In this study, chemical activation was carried out using chemical activators ZnCl2 and NaOH. The purpose of this study is to prepare and investigate the characteristics of chemically activated coffee skin bio-char focusing on the surface properties and iodine adsorption capacity. Prior to carbon activation, a purpose built pilot-scale reactor was fabricated and tested at temperatures of 400 C and 500 C. The difference in carbonation temperature and variations in activator concentration alter the absorption properties. The results showed that the coffee-skin pyrolyzed at 500 C and activated by 2% NaOH solution exhibits the highest absorption value of 720.2 mg/g. Lower absorption values were observed in any ZnCl2 activator samples. SEM-EDS analysis result suggests significant changes in composition of the ACs before and after activation. Most of impurities are gone during activation and washing. The value of C atoms increases and the pores structure of the activated carbon are expanding showing suitable properties for adsorbent.